EFEKTIVITAS PERPADUAN MEDIA KOMIK DENGAN PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA SD - Darmanto Darmanto (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Many studies have shown the advantages of comic media and Student Team Achievement Division (STAD) learning. The purpose of this study was to find out whether comic media can effectively improve learning activities and outcomes in class VI (six) students of SDN 7 Pulau Rimau if combined with STAD learning. The method used in this study is a descriptive quantitative approach involving 18 students. From the study, the results showed that the application of comic media in STAD learning in terms of the level of student activity, teacher activity, and student responses and student learning completeness turned out to be more increasing.